PERANCANGAN AUDIO VISUAL “CORPORATE PROMOTION” PADA PERUSAHAAN ASURANSI JIWA BUMI ASIH JAYA - Yeyen Oviona; Ariusmedi .; Heldi . (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstract Target of scheme is to Developing promotion media which related to company of life insurance of BAJ with approach base on visual audio and Create new promotion media to company. This scheme use model of prosedural having the character of is descriptive. Scheme process which the prosedural orient at giving of information at society. In scheme of this visual audio  needing primary data and data of skunder later then data which have in obtaining to be analysed to use method of SWOT. Scheme yield especial media which in the form of visual audio which is duration three minute eighteen second in format ofdvd presenting to display insurance information. Visual audio use promotion scene visualisation comprise about easy to its reach location, later then giving dubing voice to assure the truth of insurance of BAJ. equiped by especial Media Promotion of supporter media for example poster, sticker, calendar, pin, clothes , umbrella, banner, wall clock, Lable cd, and Mug. Kata Kunci: Perancangan Audio visual asuransi jiwa